2007
DOI: 10.1002/anie.200700428
|View full text |Cite
|
Sign up to set email alerts
|

Gold in a Metallic Divided State—From Faraday to Present‐Day Nanoscience

Abstract: “Very minute in their dimensions” is how Faraday described the metal particles present in a fine dispersion of colloidal gold upon observing its interaction with red light 150 years ago (see picture for a laser‐light version of his experiment). This observation would come to serve as the basis for the modern nanoscience and nanotechnology of gold, including the use of gold nanoparticles in catalytic processes and the formation of self‐assembled monolayers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
85
0
2

Year Published

2008
2008
2021
2021

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 166 publications
(90 citation statements)
references
References 64 publications
3
85
0
2
Order By: Relevance
“…Whereas bulk gold is a symbol of chemical inertness (2), many following studies have confirmed the size-dependent reactivity of deposited gold clusters (3)(4)(5)(6). Small particles of gold differ from the bulk as they contain edge atoms that have low coordination (7) and can adopt binding geometries which lead to a more reactive electronic structure (8).…”
mentioning
confidence: 99%
“…Whereas bulk gold is a symbol of chemical inertness (2), many following studies have confirmed the size-dependent reactivity of deposited gold clusters (3)(4)(5)(6). Small particles of gold differ from the bulk as they contain edge atoms that have low coordination (7) and can adopt binding geometries which lead to a more reactive electronic structure (8).…”
mentioning
confidence: 99%
“…11,12 Deste então, o interesse nestas NPs tem aumentado e novas metodologias de síntese e caracterização têm sido desenvolvidas, possibilitando grande controle de tamanho e formato. [13][14][15] A pesquisa nesta área foi enriquecida pela compreensão do efeito da ressonância de plasmon de superfície localizado (LSPR), que explica o comportamento óptico destes materiais. Mie foi o primeiro a elucidar a origem das cores nestas estruturas e sua teoria foi posteriormente complementada com os modelos de Maxwell-Garnett que explicavam a interação de NPs-M com o meio.…”
Section: Introductionunclassified
“…In the past, large pieces of materials coloured by gold nanoparticles have been realized; one can cite the famous Lycurgus Cup (400 AD) [14][15][16] or the stained glass of the Cathédrale Notre Dame de Paris [17][18][19] (France). These pieces were realized by master glassmakers using gold salts.…”
Section: Introductionmentioning
confidence: 99%